Logical Time for Decentralized Control of Material Handling Systems - Seibold, Zäzilia (Wissenschaftliche Berichte des Instituts für Fördertechnik und Logistiksysteme des Karlsruher Instituts für Technologie, 2016)
The fourth industrial revolution aims to transform production systems. In this work, Logical Time which is a control principle for distributed systems is transferred to material handling systems with decentralized control. The GridSorter, a modular sorter with grid-like structure, is chosen as showcase system. The system is proven to be deadlock-free and is robust against varying transport times. The time-window-based route reservation process is described as Iterative Deepening A*.